TOMAT BIKE (Automatic Bike) untuk Stimulasi pada Gangguan Sistem Gerak - Annisa annisa; Arisul Mahdi; Ahlul Aulianur; Fairuz Luthfiyah (Universitas Negeri Padang, 2019)
ABSTRACTThis article discuss about innovation of making a therapy to stimulation on the system disordes motion. The TOMAT BIKE or automatic bikes is a bicycle with pedaling automated in design in such a way, so it can be used by an individual who experience system disorders motion. Metodh used is Assembling Metodh that is process merging into some parts to from a construction. The process of assembly a starting from the choice of materials, making a prototipe, testing tools and evaluation. The results of making a tool is an individual who experience problems motion can use TOMAT BIKE and making of Intellectual Property Right (HKI) or copyright.